Preparation method and application of host-guest composite material based on non-heme iron complex and UiO-66
Through the non-heme iron complex and the host and guest composite of UiO-66, the synergistic effect of the highly adjustable confined space of the porous coordination polymer and the functional mononuclear complex, the adsorption of existing porous materials to carbon monoxide is solved. The problem of insufficient quantity and selectivity has achieved efficient carbon monoxide adsorption and controllable gas separation.
Patent Information
- Application Number
- CN202411338208.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-14
AI Technical Summary
The adsorption amount of carbon monoxide by existing porous materials is not high and the selectivity is not high, making it difficult to achieve efficient multi-component gas separation, and structural disorder limits the research on the mechanism of gas adsorption and material design.
Using the host and guest composite of non-heme iron complex and UiO-66, the preparation of zirconium-based MOF and the design of mononuclear iron complex can achieve efficient adsorption and controllable desorption of carbon monoxide, and the porous coordination polymer is used. The synergistic effect of highly adjustable confined space and functional mononuclear complexes.
It realizes efficient specific adsorption and separation of carbon monoxide, improves adsorption force and selectivity, and can achieve one-step separation and purification of carbon monoxide in a multi-component mixed gas, and achieves controllable gas release through photodesorption.
Smart Images

Figure CN119303554A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation and application of mononuclear metal complexes and zirconium-based MOFs, and in particular to a preparation method and application of a host-guest composite material based on a non-heme iron complex and UiO-66. Background Art
[0002] In recent years, porous materials based on activated carbon and zeolite are more stable and have certain adsorption properties for carbon monoxide. However, due to the undesignability of their structure, there are fewer adsorption active sites in the material structure, the adsorption force is weak, the adsorption amount of carbon monoxide is not high, and it is easy to desorb uncontrollably during storage and transportation. In addition, due to the disorder of the structure, it is difficult to carry out research on the mechanism of gas adsorption, so it is difficult to establish a structure-activity relationship and it is impossible to achieve the design and synthesis of subsequent high-performance materials. In recent years, a series of new three-dimensional ordered porous coordination polymers (PCPs) formed by coordination between metal ions and organic ligands, also known as metal-organic framework materials (MOFs), have received great attention from researchers. Especially in the field of gas adsorption and separation, porous coordination polymers have shown advantages that traditional porous materials cannot match, mainly due to the following four characteristics: (1) Through the grid chemistry strategy, the pore size can be controlled. (1) precise control of the molecular sieve effect to achieve effective separation of gas molecules; (2) through the open site design of the metal node and the functional group modification of the organic ligand, the chemical environment of the pore surface can be directly controlled; (3) the flexibility of its structure (open-close gate effect and breathing effect) can be used to achieve target molecule recognition and then achieve gas separation; (4) due to the high order and crystallinity of its structure, the adsorption sites of gas molecules can be visualized by experimental techniques such as X-ray / neutron / synchrotron radiation diffraction of single crystals or powders, and accurate structure-activity relationship can be established to guide the design and synthesis of efficient adsorption and separation materials. Based on the above advantages, porous coordination polymers have shown excellent separation effects in various gas separation fields in recent years.
[0003] In 2014, Professor Jeffrey R. Long's research group designed and synthesized a series of porous coordination polymers MOF-74-M (M = Mg, Mn, Fe, Co, Ni, Zn) based on divalent transition metals. The study found that this series of porous materials all showed a high adsorption capacity for carbon monoxide, among which MOF-74-Ni had the strongest adsorption force for carbon monoxide (-52.7 kJ mol-1, Ni-C bond length is ), and based on the IAST (Ideal Absorption Solution Theory) theory, it was predicted that the separation ratio of this material for CO / N2 was about 2000-5000, and the separation ratio of CO / H2 was 155-500, which was the highest record value for the separation ratio of the above two groups of gases at that time. However, recently, the research group of Timo Thonhauser and Kui Tan found that although the MOF-74 series has a high adsorption capacity for carbon monoxide, its selectivity is not high, and it is not suitable for direct application in the adsorption separation of multi-component gases containing CO. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing and applying a host-guest composite material based on a non-heme iron complex and UiO-66, which uses a highly adjustable confined space of a porous coordination polymer to completely physically isolate two mononuclear iron complexes, thereby greatly keeping their active sites exposed to carbon monoxide and achieving efficient adsorption of carbon monoxide.
[0005] To achieve the above object, the present invention provides a method for preparing a host-guest composite material based on a non-heme iron complex and UiO-66, comprising:
[0006] Step 1. Preparation of zirconium-based MOFUiO-66; dissolving an organic bridging ligand and a soluble zirconium salt in hydrochloric acid and N,N-dimethylformamide to obtain a mixed solution I; heating, keeping warm, cooling, washing and drying the mixed solution I to obtain a white UiO-66 powder;
[0007] Step 2. Mononuclear iron complex [(N4Py)Fe Ⅱ Preparation of [(N4Py)Fe]Cl; dissolving the organic ligand in anhydrous methanol, adding a soluble divalent iron salt, and stirring to obtain a mixed solution II, adding a poor solvent to the mixed solution II and bathing in ice water to obtain [(N4Py)Fe Ⅱ Cl]Cl orange powder;
[0008] Step 3. Composite: [(N4Py)Fe Ⅱ The Cl]Cl powder is dissolved in N,N-dimethylformamide to obtain a mixed solution III. The UiO-66 prepared in step 1 is added to the mixed solution III, the temperature is raised to 80-100°C, stirred for 8-15 minutes, and then allowed to stand at 80-95°C for 5-8 hours. The mother liquor is removed by centrifugation and washed to obtain FeN4Py@UiO-66 red powder.
[0009] Preferably, the organic bridging ligands in step 1 are terephthalic acid and benzoic acid, and the soluble zirconium salt is zirconium chloride.
[0010] Preferably, the molar ratio of phthalic acid, benzoic acid and zirconium chloride is 1:10:1.
[0011] Preferably, in step 1, the mixed solution I is heated to 110-130° C. and kept warm for 45-51 hours. After the reaction is completed, it is naturally cooled to room temperature, and then washed and dried to obtain white UiO-66 powder.
[0012] Preferably, the volume ratio of hydrochloric acid to N,N-dimethylformamide in the mixed solution I is 1:108.
[0013] Preferably, in step 2, the organic ligand is N4Py, the soluble divalent iron salt is ferrous chloride tetrahydrate, and the molar ratio of N4Py to ferrous chloride tetrahydrate is 1:1.
[0014] Preferably, in step 3, [(N4Py)Fe Ⅱ The molar ratio of Cl]Cl to UiO-66 is 1:0.376.
[0015] Preferably, in step 2, after stirring for 1-3 hours, a mixed solution II is obtained, and a poor solvent, ice, is added to the mixed solution II and the mixture is bathed in water for 10-14 hours to obtain [(N4Py)Fe Ⅱ Cl]Cl orange powder.
[0016] Preferably, the poor solvent is diethyl ether.
[0017] A composite material prepared according to any preparation method is used as a CO gas adsorbent.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] Synthesis of high-efficiency and specific carbon monoxide adsorption materials: Unlike most carbon monoxide adsorption and separation methods that use metal ions to adsorb carbon monoxide, this application can utilize the high adsorption reaction activity and photochemical release characteristics of functional bionic mononuclear complexes in the pores for carbon monoxide to achieve a one-step separation and purification of carbon monoxide in a multi-component mixed gas.
[0020] Host-guest material assembly design of functional mononuclear transition metal complexes and porous coordination polymers: Different from previous gas adsorption and separation studies that focused more on the structural modification of the porous materials themselves, this application proposes a host-guest construction strategy of "porous material framework host + functional mononuclear complex guest" to achieve specific adsorption and separation of carbon monoxide gas, in which the porous material serves as a stable external rigid "stage" and the functional transition metal complex serves as the talented internal "dancer", and the two work synergistically to achieve specific adsorption and separation of carbon monoxide. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the spectrum of FeN4Py before and after absorbing carbon monoxide;
[0022] Figure 2 This is the absorbance change spectrum of FeN4Py at 380nm and 468nm before and after absorbing carbon monoxide;
[0023] Figure 3 The color change of UiO-66 before and after loading FeN4Py complex;
[0024] Figure 4 To load FeN4Py complex into UiO-66 by immersion method, XRD patterns of UiO-66 after immersion for 1d, 3d and without immersion;
[0025] Figure 5 To load FeN4Py complex into UiO-66 by soaking method, TG spectra of UiO-66 soaked for 1d, soaked for 3d and unloaded;
[0026] Figure 6 This is the change spectrum of FeN4Py@UiO-66 after absorbing carbon monoxide for different time periods;
[0027] Figure 7 This is a characterization diagram of the assembly results of mononuclear iron complex and porous coordination polymer. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0029] This application uses non-heme mononuclear iron complexes as guest molecules and porous coordination polymers as the main framework. The host-guest system is synthesized by the host-guest assembly method, and the high adsorption reaction activity of functional guest molecules to carbon monoxide and the photo-induced desorption functionality are used to achieve efficient adsorption and green controllable desorption of carbon monoxide in the confined pores of the main material. The specific research content is divided into the following four aspects: (1) Design and synthesis of the host-guest system "(L)Fe-X@PCP" based on non-heme mononuclear iron complexes and porous coordination polymers; (2) Research on the adsorption / separation of carbon monoxide and various mixed component gases under static thermodynamic conditions and dynamic competitive conditions; (3) Research on the controllable photo-induced release performance of carbon monoxide by host-guest system materials; (4) Research on the microscopic adsorption and separation mechanism of carbon monoxide gas inside the target host-guest material.
[0030] This embodiment provides a method for preparing a host-guest composite material based on a non-heme iron complex and UiO-66, such as Figure 7 Shown include:
[0031] Step 1. Preparation of zirconium-based MOF UiO-66; dissolving an organic bridging ligand and a soluble zirconium salt in hydrochloric acid and N,N-dimethylformamide to obtain a mixed solution I; heating, heat preservation, cooling, washing and drying the mixed solution I to obtain a white UiO-66 powder; in this embodiment, the organic bridging ligand is terephthalic acid and benzoic acid, and the soluble zirconium salt is zirconium chloride;
[0032] Specifically, during the preparation, terephthalic acid, benzoic acid and zirconium chloride are dissolved in hydrochloric acid and N, N-dimethylformamide in a molar ratio of 1:10:1, wherein the volume ratio of hydrochloric acid to N, N-dimethylformamide is 1:108; a mixed solution I is obtained, the mixed solution I is heated to 110-130° C., and kept warm for 45-51 hours, and after the reaction is completed, it is naturally cooled to room temperature, and then washed and dried with N, N-dimethylformamide (DMF) to obtain a white UiO-66 powder;
[0033] Step 2. Mononuclear iron complex [(N4Py)Fe Ⅱ Preparation of [(N4Py)Fe]Cl; dissolving an organic ligand in anhydrous methanol, wherein the organic ligand in this embodiment is N4Py, adding a soluble divalent iron salt, wherein the soluble divalent iron salt in this embodiment is ferrous chloride tetrahydrate, and stirring to obtain a mixed solution II, adding a poor solvent to the mixed solution II and performing an ice-water bath to obtain [(N4Py)Fe]Cl; Ⅱ Cl]Cl orange powder;
[0034] Specifically, during the preparation, N4Py is dissolved in anhydrous methanol, and ferrous chloride tetrahydrate is added, the molar ratio of N4Py to ferrous chloride tetrahydrate is 1:1, and the mixture is stirred at room temperature for 1-3 hours to obtain a mixed solution II, and ether is added to the mixed solution II and ice-water bathed for 10-14 hours to obtain [(N4Py)Fe Ⅱ Cl]Cl orange powder
[0035] Step 3. Composite: [(N4Py)Fe Ⅱ Cl]Cl powder was dissolved in N,N-dimethylformamide to obtain mixed solution III, and UiO-66 prepared in step 1 was added to the mixed solution III, wherein [(N4Py)Fe Ⅱ The molar ratio of Cl]Cl to UiO-66 is 1:0.376; the temperature is raised to 80-100°C, stirred for 8-15 minutes, and then allowed to stand at 80-95°C for 5-8 hours, the mother liquor is removed by centrifugation, and washed with ultrapure water to obtain FeN4Py@UiO-66 red powder.
[0036] Example 1
[0037] Step 1. Preparation of zirconium-based MOF UiO-66; dissolving an organic bridging ligand and a soluble zirconium salt in hydrochloric acid and N,N-dimethylformamide to obtain a mixed solution I; heating, heat preservation, cooling, washing and drying the mixed solution I to obtain a white UiO-66 powder; in this embodiment, the organic bridging ligand is terephthalic acid and benzoic acid, and the soluble zirconium salt is zirconium chloride;
[0038] Specifically, during the preparation, terephthalic acid, benzoic acid and zirconium chloride are dissolved in hydrochloric acid and N, N-dimethylformamide in a molar ratio of 1:10:1, wherein the volume ratio of hydrochloric acid to N, N-dimethylformamide is 1:108; a mixed solution I is obtained, the mixed solution I is heated to 120° C. and kept warm for 48 hours, and after the reaction is completed, it is naturally cooled to room temperature, and then washed and dried with N, N-dimethylformamide (DMF) to obtain a white UiO-66 powder;
[0039] Step 2. Mononuclear iron complex [(N4Py)Fe Ⅱ Preparation of [(N4Py)Fe]Cl; dissolving an organic ligand in anhydrous methanol, wherein the organic ligand in this embodiment is N4Py, adding a soluble divalent iron salt, wherein the soluble divalent iron salt in this embodiment is ferrous chloride tetrahydrate, and stirring to obtain a mixed solution II, adding a poor solvent to the mixed solution II and performing an ice-water bath to obtain [(N4Py)Fe]Cl; Ⅱ Cl]Cl orange powder;
[0040] Specifically, during the preparation, N4Py was dissolved in anhydrous methanol, and ferrous chloride tetrahydrate was added, the molar ratio of N4Py to ferrous chloride tetrahydrate was 1:1, and the mixture was stirred at room temperature for 2 hours to obtain a mixed solution II, and ether was added to the mixed solution II and ice-water bathed for 12 hours to obtain [(N4Py)Fe Ⅱ Cl]Cl orange powder
[0041] Step 3. Composite: [(N4Py)Fe Ⅱ Cl]Cl powder was dissolved in N,N-dimethylformamide to obtain mixed solution III, and UiO-66 prepared in step 1 was added to the mixed solution III, wherein [(N4Py)Fe Ⅱ The molar ratio of Cl]Cl to UiO-66 is 1:0.376; the temperature is raised to 90°C, stirred for 10 minutes and then allowed to stand at 90°C for 6 hours, the mother liquor is removed by centrifugation, and washed with ultrapure water to obtain FeN4Py@UiO-66 red powder.
[0042] Example 2
[0043] Step 1. Preparation of zirconium-based MOF UiO-66; dissolving an organic bridging ligand and a soluble zirconium salt in hydrochloric acid and N,N-dimethylformamide to obtain a mixed solution I; heating, heat preservation, cooling, washing and drying the mixed solution I to obtain a white UiO-66 powder; in this embodiment, the organic bridging ligand is terephthalic acid and benzoic acid, and the soluble zirconium salt is zirconium chloride;
[0044] Specifically, during the preparation, terephthalic acid, benzoic acid and zirconium chloride are dissolved in hydrochloric acid and N, N-dimethylformamide in a molar ratio of 1:10:1, wherein the volume ratio of hydrochloric acid to N, N-dimethylformamide is 1:108; a mixed solution I is obtained, the mixed solution I is heated to 110° C., and kept warm for 51 hours, and after the reaction is completed, it is naturally cooled to room temperature, and then washed and dried with N, N-dimethylformamide (DMF) to obtain a white UiO-66 powder;
[0045] Step 2. Mononuclear iron complex [(N4Py)Fe Ⅱ Preparation of [(N4Py)Fe]Cl; dissolving an organic ligand in anhydrous methanol, wherein the organic ligand in this embodiment is N4Py, adding a soluble divalent iron salt, wherein the soluble divalent iron salt in this embodiment is ferrous chloride tetrahydrate, and stirring to obtain a mixed solution II, adding a poor solvent to the mixed solution II and performing an ice-water bath to obtain [(N4Py)Fe]Cl; Ⅱ Cl]Cl orange powder;
[0046] Specifically, during the preparation, N4Py was dissolved in anhydrous methanol, and ferrous chloride tetrahydrate was added, the molar ratio of N4Py to ferrous chloride tetrahydrate was 1:1, and the mixture was stirred at room temperature for 3 hours to obtain a mixed solution II, and ether was added to the mixed solution II and ice-water bathed for 14 hours to obtain [(N4Py)Fe Ⅱ Cl]Cl orange powder
[0047] Step 3. Composite: [(N4Py)Fe Ⅱ Cl]Cl powder was dissolved in N,N-dimethylformamide to obtain mixed solution III, and UiO-66 prepared in step 1 was added to the mixed solution III, wherein [(N4Py)Fe Ⅱ The molar ratio of Cl]Cl to UiO-66 is 1:0.376; the temperature is raised to 80°C, stirred for 15 minutes and then allowed to stand at 80°C for 8 hours, the mother liquor is removed by centrifugation, and washed with ultrapure water to obtain FeN4Py@UiO-66 red powder.
[0048] Example 3
[0049] Step 1. Preparation of zirconium-based MOF UiO-66; dissolving an organic bridging ligand and a soluble zirconium salt in hydrochloric acid and N,N-dimethylformamide to obtain a mixed solution I; heating, heat preservation, cooling, washing and drying the mixed solution I to obtain a white UiO-66 powder; in this embodiment, the organic bridging ligand is terephthalic acid and benzoic acid, and the soluble zirconium salt is zirconium chloride;
[0050] Specifically, during the preparation, terephthalic acid, benzoic acid and zirconium chloride are dissolved in hydrochloric acid and N, N-dimethylformamide in a molar ratio of 1:10:1, wherein the volume ratio of hydrochloric acid to N, N-dimethylformamide is 1:108; a mixed solution I is obtained, the mixed solution I is heated to 130° C., and kept warm for 45 hours, and after the reaction is completed, it is naturally cooled to room temperature, and then washed and dried with N, N-dimethylformamide (DMF) to obtain a white UiO-66 powder;
[0051] Step 2. Mononuclear iron complex [(N4Py)Fe Ⅱ Preparation of [(N4Py)Fe]Cl; dissolving an organic ligand in anhydrous methanol, wherein the organic ligand in this embodiment is N4Py, adding a soluble divalent iron salt, wherein the soluble divalent iron salt in this embodiment is ferrous chloride tetrahydrate, and stirring to obtain a mixed solution II, adding a poor solvent to the mixed solution II and performing an ice-water bath to obtain [(N4Py)Fe]Cl; Ⅱ Cl]Cl orange powder;
[0052] Specifically, during the preparation, N4Py was dissolved in anhydrous methanol, and ferrous chloride tetrahydrate was added, the molar ratio of N4Py to ferrous chloride tetrahydrate was 1:1, and the mixture was stirred at room temperature for 1 hour to obtain a mixed solution II, and ether was added to the mixed solution II and ice-water bathed for 10 hours to obtain [(N4Py)Fe Ⅱ Cl]Cl orange powder
[0053] Step 3. Composite: [(N4Py)Fe Ⅱ Cl]Cl powder was dissolved in N,N-dimethylformamide to obtain mixed solution III, and UiO-66 prepared in step 1 was added to the mixed solution III, wherein [(N4Py)Fe Ⅱ The molar ratio of Cl]Cl to UiO-66 is 1:0.376; the temperature is raised to 100°C, stirred for 10 minutes, and then allowed to stand at 95°C for 5 hours, the mother liquor is removed by centrifugation, and washed with ultrapure water to obtain FeN4Py@UiO-66 red powder.
[0054] Example 4
[0055] A method for preparing a host-guest composite material based on a non-heme iron complex and UiO-66, comprising:
[0056] Phthalic acid and benzoic acid were used as organic bridging ligands, and zirconium chloride was used to synthesize the UiO-66 metal organic framework. The results of the carbon monoxide adsorption experiment using this organic framework are shown in Figure 2. Figure 4 and Figure 5 shown.
[0057] Specifically:
[0058] A mixture of 0.320 g (2 mmol) of terephthalic acid (H2bdc), 0.466 g (2 mmol) of zirconium chloride (ZrCl4), 2.44 g (20 mmol) of benzoic acid, 0.33 mL of hydrochloric acid (37%) and 36 mL of N, N-dimethylformamide (DMF) was sealed in a 50 mL polytetrafluoroethylene-lined stainless steel reactor, heated to 120°C and kept warm for 48 hours, and naturally cooled to room temperature after the reaction was completed; the reaction mother liquor was removed by centrifugation, and the product was washed three times with fresh DMF to obtain a white powder product.
[0059] Using N4Py as an organic ligand, the effect of using the FeN4Py complex to absorb carbon monoxide is as follows Figure 1 and Figure 2 As shown in the figure, the mononuclear iron complex [(N4Py)Fe Ⅱ Cl]Cl, specifically:
[0060] Weigh 0.441 g (0.12 mmol) of N4Py and dissolve it in 1.5 mL of anhydrous methanol. Add 0.236 g (0.12 mmol) of ferrous chloride tetrahydrate (FeCl2·4H2O). Stir at room temperature for 2 hours. Add poor solvent ether to the reaction solution and soak it in ice water for 12 hours to obtain orange [(N4Py)Fe Ⅱ Cl]Cl powder.
[0061] The FeN4Py@UiO-66 composite system was synthesized by immersion method, specifically:
[0062] Weigh 0.832 g (0.5 mmol) UiO-66 and 0.093 g (0.188 mmol) [(N4Py)Fe Ⅱ Cl]Cl was dissolved in 20 mL DMF to form a mixed solution. The solution was heated to 90°C and stirred for 10 min. Stirring was stopped and the solution was allowed to stand at 90°C for 6 hours. After the reaction was completed, the mother liquor was removed by centrifugation and the surface raw materials were removed by washing with ultrapure water three times. Finally, a light red FeN4Py@UiO-66 powder was obtained. The comparison of UiO-66 before and after loading FeN4Py is shown in the figure. Figure 3 As shown; the prepared FeN4Py@UiO-66 was used to adsorb carbon monoxide, and the effect was as follows Figure 6 shown.
[0063] In this embodiment, the highly adjustable confined space of the porous coordination polymer can completely physically isolate the two mononuclear iron complexes, thereby greatly keeping their active sites exposed to carbon monoxide and achieving efficient adsorption of carbon monoxide. At the same time, the pore structure of the porous material itself does not affect the controllable desorption process of guest molecules to carbon monoxide under near-ultraviolet light. Based on the above analysis, the porous coordination polymer and the functional transition metal complex have great application prospects for the separation of carbon monoxide gas by the host-guest assembly method.
[0064] The above embodiments are merely examples of the present invention and do not limit the protection scope of the present invention. All designs that are the same or similar to the present invention fall within the protection scope of the present invention.
Claims
1. A method for preparing a host-guest composite material based on a non-heme iron complex and UiO-66, characterized in that: include: Step 1. Preparation of zirconium-based MOF UiO-66; dissolving an organic bridging ligand and a soluble zirconium salt in hydrochloric acid and N,N-dimethylformamide to obtain a mixed solution I; heating, keeping warm, cooling, washing and drying the mixed solution I to obtain a white UiO-66 powder; Step 2. Mononuclear iron complex [(N4Py)Fe Ⅱ Preparation of [(N4Py)Fe]Cl; dissolving the organic ligand in anhydrous methanol, adding a soluble divalent iron salt, and stirring to obtain a mixed solution II, adding a poor solvent to the mixed solution II and bathing in ice water to obtain [(N4Py)Fe Ⅱ Cl]Cl orange powder; Step 3. Composite: [(N4Py)Fe Ⅱ The Cl]Cl powder is dissolved in N,N-dimethylformamide to obtain a mixed solution III. The UiO-66 prepared in step 1 is added to the mixed solution III, the temperature is raised to 80-100°C, stirred for 8-15 minutes, and then allowed to stand at 80-95°C for 5-8 hours. The mother liquor is removed by centrifugation and washed to obtain FeN4Py@UiO-66 red powder.
2. The method for preparing a host-guest composite material based on a non-heme iron complex and UiO-66 according to claim 1, characterized in that: The organic bridging ligands in step 1 are terephthalic acid and benzoic acid, and the soluble zirconium salt is zirconium chloride.
3. The method for preparing a host-guest composite material based on a non-heme iron complex and UiO-66 according to claim 2, characterized in that: The molar ratio of phthalic acid, benzoic acid and zirconium chloride is 1:10:
1.
4. The method for preparing a host-guest composite material based on a non-heme iron complex and UiO-66 according to claim 1, characterized in that: In step 1, the mixed solution I is heated to 110-130° C. and kept warm for 45-51 hours. After the reaction is completed, it is naturally cooled to room temperature, and then washed and dried to obtain white UiO-66 powder.
5. The method for preparing a host-guest composite material based on a non-heme iron complex and UiO-66 according to claim 1, characterized in that: The volume ratio of hydrochloric acid to N,N-dimethylformamide in the mixed solution I is 1:
108.
6. The method for preparing a host-guest composite material based on a non-heme iron complex and UiO-66 according to claim 1, characterized in that: In step 2, the organic ligand is N4Py, the soluble divalent iron salt is ferrous chloride tetrahydrate, and the molar ratio of N4Py to ferrous chloride tetrahydrate is 1:
1.
7. The method for preparing a host-guest composite material based on a non-heme iron complex and UiO-66 according to claim 1, characterized in that: In step 3, [(N4Py)Fe Ⅱ The molar ratio of Cl]Cl to UiO-66 is 1:0.
376.
8. The method for preparing a host-guest composite material based on a non-heme iron complex and UiO-66 according to claim 1, characterized in that: In step 2, after stirring for 1-3 hours, a mixed solution II is obtained, and a poor solvent is added to the mixed solution II and ice-water bath is carried out for 10-14 hours to obtain [(N4Py)Fe Ⅱ Cl]Cl orange powder.
9. The method for preparing a host-guest composite material based on a non-heme iron complex and UiO-66 according to claim 1 or 8, characterized in that: The poor solvent is diethyl ether.
10. Use of a composite material prepared according to any one of the preparation methods of claims 1 to 8 for CO gas adsorption separation.